2019
DOI: 10.1038/s41467-019-08573-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoelectrical response of thermodynamically epitaxial organic crystals at the two-dimensional limit

Abstract: Owing to strong light-matter interaction, two-dimensional (2D) organic crystal is regarded as promising materials for ultrasensitive photodetectors, however it still received limited success due to degraded photoelectrical response and problems in controllable growth. Here, we find the growth of 2D organic crystal obeys Gibbs-Curie-Wulff law, and develop a seed-epitaxial drop-casting method to grow millimeter-sized 1,4-bis(4-methylstyryl)benzene 2D crystals on SiO2/Si in a thermodynamically controlled process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 60 publications
0
67
0
Order By: Relevance
“…These results revealed that efficient interlayer charge transfer occurred between NDI‐C 6 and C 8 ‐BTBT at the heterojunction interface, which is the key point to charge separation in the phototransistor devices. [ 33,34 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results revealed that efficient interlayer charge transfer occurred between NDI‐C 6 and C 8 ‐BTBT at the heterojunction interface, which is the key point to charge separation in the phototransistor devices. [ 33,34 ]…”
Section: Resultsmentioning
confidence: 99%
“…Hence, to achieve efficient charge separation, the thickness of the organic photoactive layers should be less than the exciton diffusion length, which is usually on the order of ≈10 nm. [ 10–12 ] Additionally, the thick photoactive layers cannot be efficiently field‐effect modulated due to the interlayer screening effect, [ 13,14 ] which limits the device photoresponse characteristics including a slow decay of the photocurrent. Therefore, the exciton‐diffusion bottleneck must be removed to achieve high‐speed phototransistors and promote their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Semiconductor structures at subwavelength scale naturally possess optical resonances, which provides the possibility to manipulate light–matter interactions. [ 12–20 ] Recently, many researches based on resonance structures have been carried out to improve the performance in optical instrument photodetectors and solar cells. [ 14,21–23 ] Studies of the resonance structures mainly focus on the characteristics of spherical particles or circular cylinders, which show that optical responses can be regulated with controllable Mie scattering based light–matter interaction.…”
Section: Figurementioning
confidence: 99%
“…The resonant modes from the enlarged cross section can interact more effectively with the incident light, depending on the antenna effect of the nanostructures. [ 15–20 ] In previous studies, nanostrip‐based photodetectors exhibit a strong angle‐dependent optical response due to the difference of resonance strength between 1D structure and light with different incident angles. [ 15,25 ] The square cross section of nanostrips in the light determines the strengths of resonant and nonresonant channels.…”
Section: Figurementioning
confidence: 99%
“…Since the successful exfoliation of monoatomic graphene by Novoselov et al [3] in 2004, a series of inorganic 2DMs, including transition-metal dichalcogenides (TMDs) [4], hexagonal boron nitride (h-BN) [5], metal nanomaterials [6], black phosphorus (BP) [7], and graphdiyne [8], have been obtained and investigated by fundamental studies in the fields of optoelectronics, catalysis, and energy storage [9][10][11][12][13][14]. Organic 2DMs, such as organic small molecules, polymers, and organic-inorganic hybrid materials, are emerging material systems currently attracting increasing attention owing to their unique advantages of a wide diversity of organic substrates, easily tunable properties/ functionalities, and diversified syntheses at low cost and high efficiency [15][16][17][18][19][20][21][22][23]. Among the 2DMs, 2D conjugated polymers (2DCPs) with long-range periodic covalently bonded structures and fully-extended conjugations have received special attention from scientists working in different fields.…”
mentioning
confidence: 99%